Transition from Child and Adolescent to Adult Mental Health Services in Young People with Depression: On What Do Clinicians Base their Recommendation? - van Bodegom, Larissa S.; Overbeek, Mathilde M.; Gerritsen, Suzanne E.; Maras, Athanasios; Hillegers, Manon H. J.; Wolke, Dieter; Rizopoulos, Dimitris; Allibrio, Giovanni; van Amelsvoort, Therese A. M. J.; Appleton, Rebecca; Armando, Marco; Franić, Tomislav; et al. (Depression and Anxiety, 2023)
Background. Clinicians in Child and Adolescent Mental Healthcare Services (CAMHS) face the challenge to determine who is at risk of persistence of depressive problems into adulthood and requires continued treatment after reaching the CAMHS upper age limit of care-provision. We assessed whether risk factors for persistence were related to CAMHS clinicians’ transition recommendations. Methods. Within the wider MILESTONE cohort study, 203 CAMHS users were classified with unipolar depressive disorder by their clinician, and 185 reported clinical levels of depressive problems on the DSM-oriented Depressive Problems scale of the Achenbach Youth Self Report. Logistic regression models were fitted to both subsamples to assess the relationship between clinicians’ transition recommendations and risk factors for persistent depression. Results. Only clinician-rated severity of psychopathology was related to a recommendation to continue treatment for those classified with unipolar depressive disorder (N=203; OR=1.45, 95% CI (1.03–2.03), p=.044) and for those with self-reported depressive problems on the Achenbach DSM-oriented Depressive Problems scale (N=185; OR=1.62, 95% CI (1.12–2.34), p=.012). Conclusion. Transition recommendations and need for continued treatment are based on clinical expertise, rather than self-reported problems and needs.